Influence of arthrocentesis irrigation volume at temporomandibular disorder treatment - Maysa Nogueira De Barros Melo; Josiane Nascimento Dos Santos Melo; Viviane Almeida Sarmento; Roberto Almeida De Azevedo; Christiano Sampaio Queiroz (Wolters Kluwer Medknow Publications, 2017)
Introduction: Temporomandibular disorder (TMD) treatment varies from conservative therapy to invasive procedures such as arthrocentesis. The procedure is simple and has speed, low cost, low morbidity and good patient acceptance. Literature variations, however, have been found about the type and volume of the solution used for the irrigation of temporomandibular joint (TMJ). Subjects and Methods: The aim of this study was to compare the results provided by two different volumes of 0.9% saline solution (100 ml and 250 ml) used in arthrocentesis technique for TMD treatment. It included patients unresponsive to conservative treatment. Preoperative (T0) and postoperative evaluations were performed at T1 (30th day), T2 (60th day), and T3 (90th day), in which maximal mouth opening (MMO), pain, and the presence or absence of joint sounds were recorded. Patients were randomized into two groups: 1 - submitted to arthrocentesis using 100 ml of 0.9% saline solution in TMJ and 2 - arthrocentesis performed using 250 ml of 0.9% saline solution in each TMJ. Data were submitted to descriptive and comparative analyses for each parameter per group and between groups. The effect size was calculated according to Cohen test. Minimum detectable change (MDC) was obtained and the sensibility was calculated. A statistical significance of 5% was established. Group 1 obtained increase in MMO and decrease in pain (statistically significant); in Group 2, pain decreased significantly. In Group 1, clicking decreased significantly. No statistical differences were found between groups (P = 0.333). MMO and pain results exceeded MDC, and sensibility was good. Conclusion: In conclusion, arthrocentesis is effective in TMD symptoms' relief, without statistical difference between the volumes used.